Glycated haemoglobin as an index of glycaemic control: ethnic variation among patients with type 2 diabetes mellitus in a Malaysian tertiary hospital - Ariffin, Adilah; Thambiah, Subashini C.; Abdullah, Hafizah; Samsudin, Intan Nureslyna; Zahari Sham, Siti Yazmin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Previous studies have revealed ethnic differences in glycated haemoglobin (HbA1c) value at the same glucose concentration. This study aimed to determine ethnic variation in HbA1c as an index of glycaemic control among type 2 diabetes mellitus (T2DM) patients. Methods: This cross-sectional, retrospective study recruited 293 T2DM patients by simple random sampling at the medical outpatient clinic of a tertiary hospital. Results: Ethnicity was equally distributed with 33.4% Malays and Indians, respectively, and 33.1% Chinese. Significant difference in ethnicity was noted between HbA1c groups 6.5% and >6.5%. Indians had the highest median HbA1c (8.3%), followed by Malays (7.7%) and Chinese (7.2%) [p=0.004]. Malays had lower HbA1c compared with Chinese at low- er fasting plasma glucose (FPG) whereas Chinese had lower HbA1c compared with Malays at higher FPG, crossing over at FPG 2.8 mmol/L. Indians had higher HbA1c compared with Chinese and Malays except at FPG cross-over of 16 mmol/L where Malays were higher than Indians. FPG and ethnicity were independent predictors of HbA1c. An increase of 1 mmol/L in FPG resulted in an increase of 0.44% in HbA1c. Indians and Malays had 0.60% and 0.47% higher HbA1c, respectively, than Chinese. Conclusion: This pilot study in Malaysia examined ethnic variation in the relationship between FPG and HbA1c among T2DM patients. Since HbA1c is higher in Indians and Malays compared with Chinese at any given FPG, the hypoglycaemia risk may be increased in Indians and Malays when treatment strategies are focussed on using similar target HbA1c values to treat them.